3D Electronics: 3D Sidewall Integration of Ultrahigh‐Density Silicon Nanowires for Stacked Channel Electronics (Adv. Electron. Mater. 7/2019). (9th July 2019) - Wu, Xiaoxiang; Ma, Haiguang; Yin, Han; Pan, Danfeng; Wang, Junzhuan; Yu, Linwei; Xu, Jun; Shi, Yi; Chen, Kunji
Abstract : In article number 1800627, Kunji Chen and co‐workers demonstrate 3D sidewall growth and integration of ultra‐long parallel silicon nanowires along oblique and vertical grooves. This procedure enables reliable low‐temperature fabrication of multilevel stacked‐channel field effect transistors. Such transistors demonstrate high I on / I off current ratio >10 7 and rather low leakage current, paving the way for the construction of more advanced 3D electronics.